Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Inner-body governing mechanisms for shear-driven gas leakage flow over a ventilated supercavity - Wang Zou; Jiaming Wang; Liuxuan Li; Chongguang Wang; Hanyu Gan; Hanxu Qiu (Ocean Engineering, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Br radicals generated via bromate-free photoactivation may promote degradation of emerging contaminants in highly saline waters - Min Zhao; Jiaming Gan; Yingdong Li; Mingbao Feng; Hamid Mohammed Al-Gabr; Xin Yu; Lei Wang (Water Research, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Kinematic Stability Analysis of Anchor Cable Structures in Submerged Floating Tunnel under Combined Parametric–Vortex Excitation - Jiaming Xiong; Song Sang; Youwei Du; Chaojie Gan; Ao Zhang; Fugang Liu (Journal of Marine Science and Engineering, 2024)
The submerged floating tunnel is a marine transportation infrastructure that links two shorelines. The tunnel tube body’s buoyancy exceeds gravity, with anchoring ensuring equilibrium. Anchoring reliability is crucial. This study presents a three-way coupled kinematic model for the mooring structure, formulated on Hamilton’s principle and Kirchhoff’s assumption. It explores the impact of the tube body’s buoyancy-to-weight ratio and the sea current’s angle of incidence on mooring motion response. By solving the motion analysis model, Hill’s equation system is derived to assess the parameter instability of the anchor cable structure. The coefficient of excitation instability intervals for the submerged floating tunnel is determined and validated. The findings indicate the following: (1) Increasing the float-weight ratio reduces displacement response amplitudes in all directions, bringing downstream and transverse currents closer to their initial positions; (2) Changes in current direction angles result in decreased downstream excitation strength and increased transverse displacement response with the same excitation direction; (3) The instability interval visualization effectively predicts anchor cable structure instability under parametric excitation. Structures within the instability region are deemed unstable, while those outside are considered stable.

Effect of Stratified Flow on the Vibration of Anchor Cables in a Submerged Floating Tunnel - Jiaming Xiong; Song Sang; Xiao Shi; Chaojie Gan (Journal of Marine Science and Engineering, 2024)
This study investigates the vertical-type submerged floating tunnel with anchor cables. Based on the characteristics of the anchor cables, the anchor cables are simplified as a nonlinear beam model with hinged ends. Disregarding the axial displacement of the tunnel body, the loads will cause displacements in the x and z directions of the tunnel body. The vibrations of the anchor cables are decomposed into three directions, and the parameter excitation at the connection point between the anchor cables and the tunnel body is taken into account. The equations of motion for the three degrees of freedom of the anchor cables are established using Hamilton’s principle, and then the three equations are solved using the Galerkin method and the fourth-order Runge–Kutta method. The basic characteristics of an internal wave stratified flow acting on the anchor cables are considered, as well as the influence of the incident angle of the ocean currents on the three degrees of freedom of the anchor cables. The results indicate that (1) stratified flow weakens the first- and third-order vortex-induced vibrations of the anchor cables while enhancing the second-order vortex-induced vibrations. When considering the parameter excitation of the anchor cables, the first- and third-order vibrations are weakened, while the second-order vibration remains significant; (2) the first-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency, and the second-order vibration of the anchor cables reaches its maximum value when the transverse oscillation frequency of the tunnel body is twice its natural frequency; (3) the downstream vibration of the anchor cables increases with the increase in the incident angle of the ocean currents, the cross-flow vibration of the anchor cables decreases with the increase in the incident angle of the ocean currents, and the axial vibration of the anchor cables reaches its maximum value when the incident angle of the ocean currents is 60 degrees; (4) stratified flow weakens the lock-in phenomenon of the anchor cables, and the influence of the 1/2 stratified flow on the vibrations of the anchor cables is greater than the influence of the 1/2 stratified flow.

Kinetic modeling and mechanisms of parahalogenated phenols degradation by UV222/H2O2 - Min Zhao; Ting Li; Yizhan Zhang; Jiaming Gan; Yiting Zhao; Xin Yu; Lei Wang (Journal of Cleaner Production, 2024)

Degradation and dechlorination of trichloroacetic acid induced by an in situ 222 nm KrCl* excimer radiation - Jiaming Gan; Ting Zhu; Yizhan Zhang; Dailin Li; Ting Li; Min Zhao; ZengXia Zhao; Lei Wang (Chemosphere, 2023)

Superiority of UV222 radiation by in situ aquatic electrode KrCl excimer in disinfecting waterborne pathogens: Mechanism and efficacy - Ting Li; Yizhan Zhang; Jiaming Gan; Xin Yu; Lei Wang (Journal of Hazardous Materials, 2023)

An improved spatial case-based reasoning considering multiple spatial drivers of geographic events and its application in landslide susceptibility mapping - Zheng Zhao; Jianhua Chen; Jiaming Yao; Kaihang Xu; Yangyang Liao; Huawei Xie; Xianxia Gan (CATENA, 2023)